Clinical efficacy of guava (Psidium guajava L.) in human trials: A review of therapeutic and nutritional applications - Ni Pande Made Ayu Dinda Saraswati, Dinda; Purwanata, I Gede Raditya (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2023)
This review examines clinical evidence for guava's therapeutic efficacy across multiple health domains. Randomized controlled trials reveal guava's significant impacts on metabolic health, demonstrating reduced postprandial glucose responses, improved lipid profiles, and decreased blood pressure. Nutritional intervention studies establish guava as an effective food-based strategy for improving iron status in vulnerable populations through enhanced iron absorption, particularly in children and pregnant women. Additional clinical evidence supports guava's applications in musculoskeletal health (reducing knee pain), dermatological care (controlling sebum production), oral health (preventing gingivitis and reducing oral pathogens), and gastrointestinal disorders (alleviating diarrheal symptoms). These diverse therapeutic effects stem from guava's rich phytochemical profile, including flavonoids, carotenoids, and exceptionally high vitamin C content. The review highlights guava's versatility as a well-tolerated, accessible intervention that aligns with sustainable, food-based approaches to health management. While current evidence provides a foundation for guava's clinical applications, future research should further elucidate mechanisms of action, optimize preparations, and explore additional therapeutic potential. Guava emerges as a scientifically validated therapeutic agent with significant potential to improve health outcomes across diverse populations and conditions.